Interaction between Cadmium and Zinc in Triticale (X Triticosecale wittmack) Grown under Field Conditions - AKAY, AYSEN (Asian Journal of Chemistry, 2010)
An investigation of the interaction between cadmium (Cd) and zinc (Zn) in triticale, a field experiment was conducted. Cadmium and zinc at tillering stage (3-4 leaf) applied by foliar application (individually and jointly) to triticale in the following doses (in kg/da): Cd-0,1,2,4 and 6, Zn-0,1.5 and 3. Flag leaf samples were taken at heading stage, and grain samples were also taken after harvest. The concentration of Cd and Zn in flag leaves and grain was measured by ICP-AES. No phytotoxic symptoms were observed during experiment. The grain yield was used as a parameter of growth and Cd and Zn application did not affected the grain yield of triticale. Cadmium concentrations in flag leaf and grain increased with increasing Cd application but decreased with increasing Zn application. Cd and Zn application unchanged nitrogen and potassium concentration in triticale. The effect of different doses of Cd and Zn application on grain Cd content was found statistically significant. Increased Cd doses decreased Zn content in grain.